2004
DOI: 10.1126/science.1095505
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Stimulate Self-Renewal and Expand Neurogenesis of Neural Stem Cells

Abstract: Neural stem cells are reported to lie in a vascular niche, but there is no direct evidence for a functional relationship between the stem cells and blood vessel component cells. We show that endothelial cells but not vascular smooth muscle cells release soluble factors that stimulate the self-renewal of neural stem cells, inhibit their differentiation, and enhance their neuron production. Both embryonic and adult neural stem cells respond, allowing extensive production of both projection neuron and interneuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
1,101
9
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,379 publications
(1,159 citation statements)
references
References 17 publications
42
1,101
9
7
Order By: Relevance
“…In adult hippocampus and the subventricular zone, NSCs are found in close proximity to blood vessels and surrounded by glial cells. Other studies suggested that endothelial cells and astroglia cells, which express VEGF and bFGF, stimulate self-renewal and expand neurogenesis of NSCs and may serve as a niche for NSCs [19,20]. In the present study, we found that VEGF autocrine plays a role in the regulation of NSC proliferation Figure 3).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In adult hippocampus and the subventricular zone, NSCs are found in close proximity to blood vessels and surrounded by glial cells. Other studies suggested that endothelial cells and astroglia cells, which express VEGF and bFGF, stimulate self-renewal and expand neurogenesis of NSCs and may serve as a niche for NSCs [19,20]. In the present study, we found that VEGF autocrine plays a role in the regulation of NSC proliferation Figure 3).…”
Section: Discussionsupporting
confidence: 71%
“…In adults, NSCs are found in close proximity to blood vessels and surrounded by glial cells in the hippocampus and the subventricular zone. Previous studies by others suggested that both vascular cells and glial cells may serve as a niche for NSCs [19,20]. Since both cell types express VEGF and bFGF [21], we hypothesize that these two growth factors may serve as niche signals for NSCs.…”
Section: Introductionmentioning
confidence: 63%
“…Endothelial cells derived from cell lines stimulate the self-renewal of adult neural stem cells and promote their production of neurons (Shen et al, 2004). To closely mimic the in vivo condition, we isolated RBECs and SVZ cells from adult normal and stroke rat brains.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that angiogenesis and neurogenesis may have intrinsic relationships and that endothelial cells may play an important role in neurogenesis. In 2004, it was suggested that endothelial cells play an essential role in the proliferation of neural stem cells and in their differentiation into neurons (Shen et al, 2004). However, little is known about the mechanisms by which endothelial cells regulate neurogenesis.…”
Section: Introductionmentioning
confidence: 99%